Opportunities For Batik MSMEs To Indonesia's Economic Growth in The Era of Digital Culture: Batik Case Study in Semarang City, Central Java - Zulfikar, Ahya; Aisyah, Haydee Noor; Pinarsinta, Tira; Lestari, Rahayu; Hardini, Resti; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to describe Indonesia's economic growth strategy in the Digital Culture Era in providing opportunities for Micro, Small, and Medium Enterprises (MSMEs) which focuses on opportunity strategies in 5 aspects, namely Enablement, Strengthening, Protection, Support, and Maintenance. This is motivated by programs and training held by Batik 16 in Semarang City, Central Java in developing MSMEs in Semarang City. After that, researchers compared what happened to business actors. Marketing and training are the main factors in the development of MSMEs. In addition, the opportunities carried out by Batik 16 must be optimized by increasing competitive and innovative human resources. The results of this study show that MSME opportunities carried out by Batik 16 Semarang City and the programs and training carried out have been effective and beneficial for business actors